THE EFFECT OF ELECTRIC CURRENT SEVERITY AND ELECTRIC SHOCK TIMING ON VEGETATIVE AND FLOWERING CHARACTERISTICS OF Iris hollandica - Sami K.M. Ameen (Mesopotamia Journal of Agriculture)
The study was conducted in the lathhouse of Horticulture Department – College of Agri. Baghdad University at Fall season 2005 to investigate the effect of electric field on the vegetative flowering and bulbs growth characters of Iris hollandica. Three levels of electric current severity AC 6, 8, 10 Ampere and three timing of electric shock 2, 4, 6 minutes were tested. A special electric apparatus was designed for this purpose. The bulbs were soaked before treatment for 3hrs in a 1% NaCl solution, then soaked in a fresh water for the same period 3hrs before planting in the soil. Bulbs which were exposed to 8 A × 6 mins significantly increased the plant height 68.18 cm., flower stem length 59.35 cm., flower stem diameter 1.45 cm. and vase life 10.23 days. While the treatment 8 A × 4 mins reduced the emerging date to 8.87 days and flowering date 112.91 days. The treatment 8 A × 2 mins increased leaf area 612.10 cm2, dry matter percentage of vegetative growth 29.12%, No. of bulblets 7.47 and total bulb weight 30.45 gm. While the flower diameter was increased to 13.00 when the bulbs exposed to 10 A × 2 mins